2013
DOI: 10.1177/1460408613488480
|View full text |Cite
|
Sign up to set email alerts
|

Blunt chest wall trauma: A review

Abstract: Blunt chest wall trauma accounts for a large proportion of all trauma presentations to the Emergency Departments in the United Kingdom and has a high reported incidence of morbidity and mortality. The difficulty in the assessment and management of this patient group arises from the possibility that the patient may develop potentially life-threatening complications up to approximately 72 h post-injury, even in patients who have sustained what is initially considered a minor injury. Limited consensus currently e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 107 publications
(198 reference statements)
0
9
0
Order By: Relevance
“…The association between advancing age, pre-existing respiratory disease and mortality in chest wall injury is well described 7. A risk score that informs the management of the elderly patient with chest wall injury should contain a measure of preinjury morbidity or frailty and include age as a key determinant of the scoring outcome.…”
Section: Can a Risk Or Severity Score Help Guide His Management?mentioning
confidence: 99%
See 1 more Smart Citation
“…The association between advancing age, pre-existing respiratory disease and mortality in chest wall injury is well described 7. A risk score that informs the management of the elderly patient with chest wall injury should contain a measure of preinjury morbidity or frailty and include age as a key determinant of the scoring outcome.…”
Section: Can a Risk Or Severity Score Help Guide His Management?mentioning
confidence: 99%
“…Elderly trauma patients with rib fractures have a more than twofold greater risk of mortality compared with those without (7.6% vs 20.1%, p=0.001) 6. The risk of death from rib fractures is two to five times greater in those aged 65 or older compared with those under 65 7–9. Data from the US National Trauma Data Bank show that at any age, the number of ribs fractured correlates with a significantly increased risk of pneumonia and/or death.…”
Section: Introductionmentioning
confidence: 98%
“…Over 11,000 patients with multiple (3) rib and/or sternal fractures are registered in the UK's Trauma Audit Research Network (TARN) database each year. 1 Over 20% of trauma presentations in the UK involve blunt chest wall trauma and the associated mortality is 22% 2 ; two-thirds of these injuries involve rib fractures. 3 The term 'multiple rib fractures' (MRFs) encompasses a wide range of injuries, from a few undisplaced, stable fractures, with little consequence, to many displaced and unstable fractures, causing chest wall disruption, respiratory failure, significant acute and chronic pain and which are associated with mechanical ventilation, lengthy critical care stays and death.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Evidence supporting surgical stabilisation of rib fractures (SSRF) is increasing. 2 Single centre randomised controlled trials have demonstrated significant clinical benefits for patients with flail chest, [11][12][13][14] but further clinical trials are required to investigate the indications in other categories of MRF injury. 15 Inconsistent description of the clinical findings with radiology pattern of injury means there is a need to clarify taxonomy.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Historically, analgesia and chest physiotherapy have been the primary methods of managing a patient with blunt chest wall trauma, with the main aim of reducing the acute risk of the development of potentially fatal pulmonary complications. [3] Longer-term complications have also been investigated and in a small study conducted by this research team, chronic pain was reported in 35% patients with a median pain severity score of 6 out of 10 (IQR: 3-7). [4] In a similar recent prospective study of 111 patients with isolated rib fractures, a prevalence of chronic pain of 64% and disability of 67% were reported.…”
Section: Introductionmentioning
confidence: 99%